Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1002/j.2050-0416.2002.tb00121.x
|View full text |Cite
|
Sign up to set email alerts
|

Gelatinisation Characteristics and Enzyme Susceptibility of Different Types of Barley Starch in the Temperature Range 48-72°C1

Abstract: The gelatinisation temperatures, pasting characteristics and enzymic susceptibilities in the temperature range 48-72°C of normal, high amylose, low amylose and zero amylose barley starches were determined. Normal starches had the lowest gelatinisation temperatures, but low and zero amylose starches had the lowest pasting temperatures. Normal starches were the most readily soluble in water at 48-60°C in the presence of a mixture of α-amylase, β-amylase and limit dextrinase and were most readily broken down to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…The results of gelatinization temperature of the two rice varieties are shown in Table I and these results agree with other reports, that non-waxy starch has a lower gelatinization temperature than waxy starch 19 . The gelatinization temperature of the malted rice was in the range of 64-66.8°C, which was lower than the unmalted form; 71°C and 73°C for black non-waxy rice and black waxy rice, respectively.…”
Section: Gelatinization Temperaturesupporting
confidence: 90%
“…The results of gelatinization temperature of the two rice varieties are shown in Table I and these results agree with other reports, that non-waxy starch has a lower gelatinization temperature than waxy starch 19 . The gelatinization temperature of the malted rice was in the range of 64-66.8°C, which was lower than the unmalted form; 71°C and 73°C for black non-waxy rice and black waxy rice, respectively.…”
Section: Gelatinization Temperaturesupporting
confidence: 90%
“…Studies on barley found that the malt qualities 3,5 , especially the extract yield 8 , depend on the endosperm components of starch and the protein and structure. During the germination and mashing process, a range of fermentable sugars, which are the main components that constitute the extract of the wort, are produced from the hydrolysis of starch 9 . Starch is composed of amylose and amylopectin.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, solubilization or gelatinization is a prerequisite of starch hydrolysis. MacGregor et al (27) found that the pasting temperatures of the starches raised with the content of amylose. However, starches with an amylose content of ca.…”
Section: Introductionmentioning
confidence: 99%